PENINGKATAN LIFE SKILL REPARASI PERALATAN LISTRIK RUMAH TANGGA BAGI PEMUDA PSAABR BUDI UTAMA LUBUK ALUNG KAB. PADANG PARIAMAN - Elfizon Elfizon; Oriza Candra; Syamsuarnis Syamsuarnis; Mukhlidi Muskhir (Universitas Negeri Padang, 2019)
This paper aims to determine the effectiveness of the implementation of household electrical appliance repair training that is applied to youth Adolescent Child Care Social Institutions in Lubuk Alung, Kabupaten Padang Pariaman. Where this paper is an evaluation of the implementation of community service activities in the PSAABR. The subject of this activity is 15 foster children who take Electricity skills in Lubuk Alung Main Budi PSAABR 2018 Period II (July - December 2018). The instrument used is a questionnaire in terms of performance and product results. The results obtained were the average performance score of 82.3, while the results of the product assessment obtained an average value of 88.75. From the achievement of student learning outcomes in mastering the training material and the competencies obtained were in the high category (45%), and very high (55%), so it was concluded that the implementation of household electrical repairs training on youths Budi Adolescent Childcare Institution Main Lubuk Alung District of Pariama has been effective